The biflavonoids, amentoflavone degrades calf thymus DNA in the presence of copper ions - Ahmed, Qamar Uddin; Malik, Arshi; Azam, Sonish; Hadi, Naghma; Azmi, Asfar Sohail; Parveen, Nazneen; Khan, Nizam Ud Din; Hadi, Sheikh Mumtaz (Elsevier Science, 2004)
Previous reports from this laboratory have shown that flavonoids including apigenin are capable of inducing oxidative DNA cleavage in the presence of copper ions. In the present report, we have examined the ability of amentoflavone, a biflavonoid which is a dimer of apigenin, to catalyze the degradation of DNA. Amentoflavone was found to degrade calf thymus DNA in the presence of Cu(II) at a rate almost twice that of apigenin. Amentoflavone was also shown to reduce Cu(II) to Cu(I) and to generate hydroxyl radicals in the presence of copper ions. In the presence of Cu(II), the absorption spectrum of amentoflavone undergoes a shift and a quenching effect indicating that the biflavonoid is capable of binding to copper ions. Amentoflavone and apigenin were isolated from Cycas rumphii and Trifolium alexandrinum, respectively. The results are discussed in relation to the putative chemopreventive mechanism of amentoflavone.